MetALD: Clinical aspects, pathophysiology and treatmentKeypoints - Jordi Gratacós-Ginès; Silvia Ariño; Pau Sancho-Bru; Ramon Bataller; Elisa Pose (JHEP Reports)
Summary: Metabolic dysfunction-associated steatotic liver disease (MASLD) and alcohol-related liver disease (ALD) are the most prevalent causes of chronic liver disease worldwide. Both conditions have many pathophysiological mechanisms in common, such as altered lipid and bile acid metabolism, and share some similar clinical features. Furthermore, metabolic risk factors and alcohol often co-exist in the same individuals and have recently been shown to act synergistically to markedly increase the risk of liver disease. Given the high prevalence and impact of this interaction, steatotic liver disease due to the combination of metabolic dysfunction and moderate-to-high alcohol intake has been termed MetALD in the new steatotic liver disease nomenclature, attracting the interest of the scientific community. Subsequent studies have investigated the prevalence of MetALD, which ranges from 1.7% to 17% in cohorts of patients with steatotic liver disease, depending on the population setting and study design. A few cohort studies have also assessed the prognosis of this patient population, with preliminary data suggesting that MetALD is associated with an intermediate risk of liver fibrosis, decompensation and mortality among steatotic liver disease subtypes. In this review article, we examine the clinical evidence and the experimental models of MetALD and discuss the clinical implications of the term for early detection and management. We provide insight into the pathophysiological mechanisms of the synergistic effect of alcohol and metabolic risk factors, possible screening strategies, the use of biomarkers and emerging models of care, as well as potential therapeutic interventions with a special focus on medications for MASLD, highlighting the most promising drugs for patients with MetALD.